Difusi Inovasi Layanan Administrasi Kependudukan Digital di Wilayah Kepulauan: Studi pada SIMPEL-DUKCAPIL Kabupaten Bengkalis - Alwan Syarofi; Ardieansyah, Ardieansyah (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
This study aims to analyze the diffusion of the SIMPEL-DUKCAPIL innovation in population administration services in Bengkalis Regency. The study employs a descriptive qualitative approach using Everett M. Rogers’ diffusion of innovation theory, which includes five attributes: relative advantage, compatibility, complexity, trialability, and observability. Data were collected through interviews, observation, documentation, and triangulation involving 19 informants consisting of officials from the Population and Civil Registration Office and service users. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results show that SIMPEL-DUKCAPIL provides relative advantages in improving time efficiency, cost savings, and service accessibility, particularly for communities in archipelagic areas. The data indicate 2,311 application users in 2025 with unequal distribution across sub-districts, along with 107 blank spot areas that hinder digital service access. The compatibility and observability dimensions are relatively strong, as the application aligns with service needs and its benefits are directly perceived by users. However, the adoption process remains suboptimal due to challenges in complexity and trialability, including low digital literacy, limited internet infrastructure, technical system issues, and user preference for face-to-face services. This study highlights that innovation diffusion in archipelagic regions is not solely determined by application quality, but also by infrastructure readiness, socialization strategies, and community digital capabilities.